Electronic Monitoring of Nonviolent Convicted Felons: An Experiment in Home Detention in Marion County, Indiana, 1986-1988 - Baumer, Terry L. ([Verlag nicht ermittelbar], 1991)
The purpose of the study was to provide information about home detention monitoring systems and to evaluate their effectiveness. The principal investigators sought to determine (1) whether electronic monitoring systems relieved some of the burdens associated with manual monitoring of home detention, such as making telephone calls and field visits, (2) how home detention affected the lifestyles of offenders, (3) whether the methods of monitoring influenced offender behavior during the program, (4) how electronic monitoring differed from manual monitoring in terms of supervision of the offenders, (5) how offenders reacted to electronic monitoring, (6) how offenders' families reacted to electronic monitoring, and (7) whether the method of monitoring influenced the probability of an arrest or subsequent contact with the criminal justice system after release from the program. Part 1 contains demographic information, such as age, race, marital status, number of children, living arrangements, employment, and education for each offender. Also included is information on the offense leading to the current case, including numbers and types of charges and convictions for both felonies and misdemeanors, recommendations and judicial disposition for the current case, and information on the criminal history of the offender. Part 2 contains data from the intake interview with the offender, such as information on the offender's family, living arrangements, education, employment, past alcohol and drug use, and expectations for the home detention program and monitoring procedures. Part 3 contains information collected in the exit interview and is similar in content to Part 2. Part 4 contains information on the program delivery (type of release from the program, violations of the program, results of tests for alcohol and drug use, errand time, payment, contacts with offenders, and the characteristics and results of the contacts with electronically monitored offenders). Part 5 is a check of criminal histories of offenders for at least one year after their release from the program.